2018
DOI: 10.3892/mmr.2018.9736
|View full text |Cite
|
Sign up to set email alerts
|

Costunolide isolated from Vladimiria�souliei inhibits the proliferation and induces the apoptosis of HepG2 cells

Abstract: Costunolide (cos) is one of the major sesquiterpenes isolated from the ethyl acetate soluble fraction of the roots of Vladimiria souliei. In order to explore the effects and molecular mechanism of cos, the anti-proliferative and apoptotic effects of cos against the human hepatoblastoma HepG2 cell line was examined in vitro in the current study. Cell viability was measured using an MTT assay, and IC 50 values (indicating the concentration required to achieve half-maximal inhibition) were calculated to detect th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Reactive oxygen species (ROS) production induced by costunolide may be the important intermediate link of mitochondrial apoptosis. Costunolide has the potential to activate extrinsic pathway or endoplasmic reticulum stress pathway [21][22][23]. Our research group will be further to explore the mechanisms of costunolide via signaling pathway (such as p53, NF-κB and Wnt/β-catenin signaling pathway) and even find the specific molecular target [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) production induced by costunolide may be the important intermediate link of mitochondrial apoptosis. Costunolide has the potential to activate extrinsic pathway or endoplasmic reticulum stress pathway [21][22][23]. Our research group will be further to explore the mechanisms of costunolide via signaling pathway (such as p53, NF-κB and Wnt/β-catenin signaling pathway) and even find the specific molecular target [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Many anti-cancer drugs inhibit tumor cell proliferation via stalling the cell cycle ( Wu et al, 2020 ). Cos was found to induce G1/S phase arrest in human esophageal carcinoma Eca-109 cells ( Hua et al, 2016b ) and induce G2/M phase arrest in human liver cancer HepG2 cells and breast cancer MDA-MB-231 cells ( Mao et al, 2019 ). Our study revealed Cos could significantly induce GC cell cycle arrest in the G2/M phase via mediated Cyclin B1, Cdc25c, and Cdk1 protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has demonstrated multiple pharmacological activities of Cos, including anti-inflammatory, anti-allergic, and anti-microbial effects ( Duraipandiyan et al, 2012 ; Park et al, 2016 ; Lee et al, 2018 ). Recent studies have found that Cos possesses anti-cancer effects against human gastric adenocarcinoma, prostate cancer, liver cancer, bladder cancer, and esophageal cancer, and promotes apoptosis of a variety of cancer cells ( Rasul et al, 2013 ; Hua et al, 2016a ; Chen et al, 2017 ; Mao et al, 2019 ; Yan et al, 2019 ). However, the molecular mechanism underlying the effects of Cos against gastric cancer cells has yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…A BCA protein assay was used to determine the protein concentration, and 10% SDS-PAGE was used to resolve protein samples (50 µg). The proteins were transferred to PVDF membranes, after which blocking, and incubation with the primary and secondary antibodies was performed as described by Mao et al (28). The following primary and secondary antibodies were used: p-PI3K (1:1,000), PI3K (1:1,000), p-Akt (1:1,000), Akt (1:1,000), cleaved-PARP (1:1,000), PARP (1:1,000), xIAP (1:1,000), CDK2 (1:1,000), P53 (1:1,000), CCNA2 (1:1,000), Caspase-3 (1:1,000), GAPDH (1:1,000) and goat anti-rabbit antibody (1:1,000).…”
Section: Methodsmentioning
confidence: 99%